Feminist Reinterpretation of the Qur’an - Nina Nurmila (Qur'an and Hadith Academic Society, 2013)
This article argues that no Qur’anic interpretation is objective. Qur’anic interpretation is influenced by the interest, values and the background of its interpreters. This article will identify some of the biases in the existing Qur’anic interpretations, which are mostly written by male scholars, on gender issues such as the first human creation and male leadership, and will re-interpret the verses from equal gender perspective. This article will also argue that the correct interpretation is the one which is closer to the fundamental teaching of Islam, mainly equality and justice. Only Allah knows the ma‘na (the real/correct meaning) of the haqiqi Qur’an, but if Muslims believe that Allah is just, then it is impossible for Allah to reveal its message in the Qur’an to support injustice. Therefore, if Muslims interpret the Qur’an to support injustice, then their interpretations may be incorrect because they contradict the nature of God, who is just.